Interstitial Duplication and Distal Deletion in a Ring Chromosome 13 with Pulmonary Atresia and Ventricular Septal Defect: A Case Report and Review of Literature - Xu, PhD, Fang; DiAdamo, BS, Autumn J.; Grommisch, BS, Brittany; Li, PhD, Peining (North American Journal of Medicine and Science, 2013)
We report on a newborn female infant with a unique ring chromosome 13. Prenatal findings include intrauterine growth restriction (IUGR); ventricular septal defect (VSD), overriding aorta, and pulmonary stenosis. Postnatal examination found mild dysmorphic features of flat fontanels and hypertelorism. Echocardiogram confirmed the diagnosis of Tetralogy of Fallot (TOF), pulmonary atresia (PA) and VSD. Cytogenetic analysis detected a mosaic pattern of a ring chromosome 13, monosomy 13 and dicentric ring chromosome in about 90%, 9% and 1% of blood lymphocytes, respectively. Oligonucleotide array comparative genomic hybridization (aCGH) analysis revealed a 28.476 Mb interstitial duplication of 13q14.11-q21.33 and a 10.217 Mb distal deletion of 13q33.2-q34. Review of the literature suggested three groups of ring chromosome 13 with variable phenotypes based on the size of 13q deletions and noted two cases of ring chromosome 13 with a distal deletion defined by genomic analysis. A heat map of ring chromosome 13 phenotypes was constructed. The present case represents a new group of ring chromosome 13 with compound segmental duplication and deletion. This study demonstrates the importance of genomic characterization of constitutional ring chromosome for better disease classification and phenotype correlation. [N A J Med Sci. 2013;6(4):208-212. DOI: 10.7156/najms.2013.0604208]